Critical of Jorge J.E. Gracia’s Hermeneutical Theory and Its Application to Interpreting Quranic Verse On The Creation of Woman - Azma Muthi'ah Qurrotu'ain; Akhmad Sulthoni; Akhmadiyah Saputra (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2025)
This research aims to critically examine the interpretive framework developed by Jorge J.E. Gracia, as applied to the interpretation of the Qur'anic verse Surah al-Nisa’ [4]: 1, which addresses the creation of women. The focus of this research is to critique the application of the hermeneutical approach in strengthening the principle of gender equality and reconstructing existing interpretations of the origins and social roles of women in the Islamic context. This qualitative analysis employs a descriptive-analytic methodology and utilizes desk research techniques for data collection and analysis. The critique is contextualized through the epistemological framework of Ulumul Qur'an, which serves as the foundational basis for Islamic interpretation. The research outlines the three functions of interpretation embodied in Gracia's hermeneutics—historical, semantic, and implicative—which feminist scholars use to reconceptualize the creation of women and their gender roles. The results indicate that this interpretive approach yields different interpretations from the perspective of classical Islamic theology. The results of this study underscore the limitations and potential risks associated with applying the Western hermeneutical paradigm in Quranic interpretation